Defending Forward : Pre-emption in the Internet of Things - Lohaus, Phillip (2019)
America’s recent shift from “active defence” to “defending forward” in cyberspace has left some observers nervous. As the attack surface of the Internet rapidly expands, however, a strategy focused solely on defence will do little to incentivise adherence to international security norms. China is particularly vulnerable in the space known as the “Internet of Things,” creating an opportunity to balance the use of carrots with sharper sticks.